2020
DOI: 10.1088/1402-4896/abb2e0
|View full text |Cite
|
Sign up to set email alerts
|

A new class of Ion-acoustic solitons that can exist below critical Mach number

Abstract: It is commonly believed that ion-acoustic solitons can only exist above the critical Mach number in a plasma system. A new class of ion-acoustic solitons that can exist below the critical Mach number is reported for the first time in a three-component plasma consisting of hot Maxwellian electrons, and two counterstreaming ion beams. The analysis is based on the Sagdeev pseudopotential technique, and considers a simple case of two counterstreaming proton beams with equal density and streaming velocity. Linear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 80 publications
6
26
0
Order By: Relevance
“…The existence of fast and slow ion-acoustic modes has been established in multi-warm ion plasma models based on linear wave theory, followed by fascinating nonlinear analyses of plasmas permeated by two counterstreaming ion beams (Lakhina et al 2020;Verheest & Hellberg 2021). Recent plasma studies, adopting a plasma-fluid formalism, have revealed that beam-permeated plasmas may not only support the conventional supersonic (superacoustic) electrostatic structures (solitary waves, SWs) but also a subsonic (subacoustic) ion-acoustic nonlinear mode propagating at a speed below the sound speed but above a certain Mach number threshold (M min ; Lakhina et al 2020;Verheest & Hellberg 2021). Interestingly, Papadopoulos et al (1971) studied the heating of counterpropagating ion beams propagating across an ambient field, based on linear theory in combination with computer simulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The existence of fast and slow ion-acoustic modes has been established in multi-warm ion plasma models based on linear wave theory, followed by fascinating nonlinear analyses of plasmas permeated by two counterstreaming ion beams (Lakhina et al 2020;Verheest & Hellberg 2021). Recent plasma studies, adopting a plasma-fluid formalism, have revealed that beam-permeated plasmas may not only support the conventional supersonic (superacoustic) electrostatic structures (solitary waves, SWs) but also a subsonic (subacoustic) ion-acoustic nonlinear mode propagating at a speed below the sound speed but above a certain Mach number threshold (M min ; Lakhina et al 2020;Verheest & Hellberg 2021). Interestingly, Papadopoulos et al (1971) studied the heating of counterpropagating ion beams propagating across an ambient field, based on linear theory in combination with computer simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A plasma-fluid model consisting of two hot counterstreaming ion beams and Maxwellian electrons was adopted by Lakhina et al (2021Lakhina et al ( , 2020, who were the first to show that SWs may exist below critical Mach number, provided that certain conditions are met. Verheest & Hellberg (2021) subsequently revisited the same model by neglecting thermal ion effects and pinpointed the crucial role played by the beam speed(s)-rather than thermal effects-in subsonic solitary wave formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the background electrons follow Maxwellian distribution, their number density in the presence of electrostatic waves with potential, f is given as (Lakhina et al 2014(Lakhina et al , 2020)…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Equation (7) represents the motion of a pseudoparticle of unit mass in a pseudopotential, S(f,M), with f and ξ, respectively depicting pseudo-displacement from the equilibrium and pseudo-time (Lakhina et al 2009;Rubia et al 2017;Lakhina et al 2020). The Sagdeev pseudopotential, S(f,M), is given by Equation ( 8) is represented in an allegorical form where the operation of a square root on a squared expression results in the same expression, e.g., ( )…”
Section: Theoretical Modelmentioning
confidence: 99%